O-16 Why do patients with palliative care needs present to the emergency department?. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Green, Emilie; Shaw, Sara; Ward, Sarah; Riley, Ben; Sattar, Henna; Brierley, Will; Harris, Tim
Abstract : Policy in many countries focuses on preventing hospital admissions at the end of life. However, little attention has been paid to the role of the emergency department (ED) in this regard, despite the fact that many hospital admissions among patients with palliative care needs originate in the ED. This paper aims to improve understanding of ED use within a palliative care context. The initial phase of this service evaluation comprised a literature review. Subsequently, the electronic records of all patients known to the specialist palliative care team at Whipps Cross hospital presenting to the ED over a three-month period were evaluated prospectively (n = 112). These quantitative data were analysed using descriptive statistics. Finally, semi-structured interviews with seven patients from this sample were conducted and thematic analysis was applied. 105 patients made 112 presentations to the ED. 53% were female; the mean age was 73. The two most common presenting complaints were shortness of breath (35%) and pain (28%). There is currently no internationally agreed definition of an appropriate ED presentation; therefore one was established for the purpose of this project. 83% of presentations were deemed to legitimately require ED management. Findings from the qualitative phase highlighted a significant lack of awareness of the availability of alternative services among patients, often resulting in disjointed, inadequate care. Difficulties with data sharing between ED and specialty teams and primary and secondary care were observed, often delaying management. Patients perceived the ED to be a safer environment than primary care, capable of providing a higher level of reassurance. This service evaluation explores the reasons for ED presentation among patients with palliative care needs from both the perspectives of healthcare professionals and service users. Findings challenge commonly held misconceptions regarding the presence of palliative patients in the ED, and direct potential changes in future service provision.